Extended modified cubic B-spline algorithm for nonlinear Fisher’s reaction-diffusion equation - H.S. Shukla; Mohammad Tamsir (Alexandria Engineering Journal, 2016)
In this paper, a new method “extended modified cubic B-spline differential quadrature method (EMCB-DQM)” is introduced by using extended modified cubic B-spline functions as test functions in the traditional differential quadrature method. The accuracy and efficiency of the method are tested in view of three numerical problems. The obtained results are compared with the exact solutions and with the results available in the literature. The simple algorithm, least computational efforts and good accuracy are the main advantages of the proposed method. Thus, the proposed method may be used as an alternative method for the numerical treatment of the nonlinear partial differential equations (PDEs). The stability analysis of the method is also carried out.